Atomistic Model of Metal Nanocrystals with Line Defects: Contribution to Diffraction Line Profile - Leonardi, Alberto; Scardi, Paolo (Frontiers in Materials, 2015)
Molecular Dynamics (MD) was used to simulate cylindrical Pd and Ir domains with ideal dislocations parallel to the axis. Results show significant discrepancies with respect to predictions of traditional continuum mechanics. When MD atomistic models are used to generate powder diffraction patterns, strong deviations are observed from the usual paradigm of a small crystal perturbed by the strain field of lattice defects. The Krivoglaz-Wilkens model for dislocation effects of diffraction line profiles seems correct for the screw dislocation case if most parameters are known or strongly constrained. Nevertheless the practical implementation of the model, i.e., a free refinement of all microstructural parameters, leads to instability. Possible effects of the experimental practice based on Line Profile Analysis are discussed.